An Integrated Approach to Conventionality and Its Implications for the Semantics of Emotion Terms - Strugielska, Ariadna (Studia Anglica Posnaniensia, 2013)
The aim of this article is to demonstrate that an integrated methodology can shed a new light on the understanding of notions inherent in contemporary conceptual approaches to linguistic analysis. One of the key ideas around which the cognitive paradigm is built is conventionality. It is assumed, however, that various strands of the cognitive enterprise view conventionality in dissimilar ways. Consequently, by extrapolating diverse interpretations of the notion, we are going to argue that certain conceptual approaches are more cognitive than others. As a result, it will be argued that a conceptual metaphor methodology, an apparently dominant approach to the semantics of emotion terms, is too coarse-grained to account for the richness of cognitive processes observable in real data. Providing a corpus-assisted verification of selected instantiations of the attributive construction, we are going to argue that a conceptual metaphor approach cannot be successfully applied within a usage-based model.